Tumor microenvironment and therapeutic response - Wu, Ting; Dai, Yun (Cancer letters, 2017)
•Tumor microenvironment (TME) influences therapeutic response and clinical outcome.•TME mediated resistance results from continuous crosstalk between tumor cells and stroma.•Targeting TME compartments could improve the effectiveness of current treatment. The tumor microenvironment significantly influences therapeutic response and clinical outcome. Microenvironment-mediated drug resistance can be induced by soluble factors secreted by tumor or stromal cells. The adhesion of tumor cells to stromal fibroblasts or to components of the extracellular matrix can also blunt therapeutic response. Microenvironment-targeted therapy strategies include inhibition of the extracellular ligand–receptor interactions and downstream pathways. Immune cells can both improve and obstruct therapeutic efficacy and may vary in their activation status within the tumor microenvironment; thus, re-programme of the immune response would be substantially more beneficial. The development of rational drug combinations that can simultaneously target tumor cells and the microenvironment may represent a solution to overcome therapeutic resistance.